2006
DOI: 10.1079/bjn20051526
|View full text |Cite
|
Sign up to set email alerts
|

A reduced protein diet induces stearoyl-CoA desaturase protein expression in pig muscle but not in subcutaneous adipose tissue: relationship with intramuscular lipid formation

Abstract: A reduced protein diet (RPD) is known to increase the level of intramuscular lipid in pig meat with a smaller effect on the amount of subcutaneous adipose tissue. This might be due to tissue-specific activation of the expression of lipogenic enzymes by the RPD. The present study investigated the effect of a RPD, containing palm kernel oil, soyabean oil or palm oil on the activity and expression of one of the major lipogenic enzymes, stearoyl-CoA desaturase (SCD) and on the level of total lipids and the fatty a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
159
6
5

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 150 publications
(191 citation statements)
references
References 50 publications
21
159
6
5
Order By: Relevance
“…However, to our knowledge, research on pigs has been limited to enzymes catalysing SFA and monounsaturated fatty-acid biosynthesis. Thus, Doran et al (2006) reported differences in responses of pig muscle and adipose tissue D9-desaturase (but not acetyl-CoA carboxylase or fatty acid synthase) to a reduced protein diet.…”
Section: -Desaturasementioning
confidence: 92%
See 1 more Smart Citation
“…However, to our knowledge, research on pigs has been limited to enzymes catalysing SFA and monounsaturated fatty-acid biosynthesis. Thus, Doran et al (2006) reported differences in responses of pig muscle and adipose tissue D9-desaturase (but not acetyl-CoA carboxylase or fatty acid synthase) to a reduced protein diet.…”
Section: -Desaturasementioning
confidence: 92%
“…Samples of pig liver (approximately 3.5 g), LD muscle and subcutaneous adipose tissue (approximately 7.5 g) were homogenised in a Tris-sucrose buffer containing 250 mM sucrose and 10 mM Tris-HCl (pH 7.4), and the microsomal fraction was isolated by differential centrifugation as described earlier (Doran et al, 2006). The microsomal pellets were re-suspended in a Tris-KCl buffer (150 mM KCl and 10 mM Tris-HCl, pH 7.4), supplemented with inhibitors of proteolytic enzymes (1.5 mM pepstatin, 1.5 mM antipain and 2 mM leupeptin).…”
Section: Isolation Of Microsomesmentioning
confidence: 99%
“…The most successful nutritional strategy in non-ruminants to dissociate fat accumulation in muscle to that in other parts of the body has been obtained with subtle protein-deficient diets (Gondret and Lebret, 2002;Doran et al, 2006;D'Souza et al, 2008 in pigs). The basis of these strategies was to restrict muscle development, but the mechanisms involved in the observed increase in IMF content remain elusive.…”
Section: Manipulating Dietary Protein Energy and Micronutrientsmentioning
confidence: 99%
“…The basis of these strategies was to restrict muscle development, but the mechanisms involved in the observed increase in IMF content remain elusive. One of the possible explanations could be that lower dietary protein levels stimulate the expression of SCD1, which catalyses the cellular biosynthesis of monounsaturated fatty acids (Doran et al, 2006). Indeed, oleic and palmitoleic fatty acids, as the main products of SCD, are the main monounsaturated fatty acids in fat depots and membrane phospholipids, and a different pattern of SCD gene isoforms may exist between muscle and subcutaneous fat tissues.…”
Section: Manipulating Dietary Protein Energy and Micronutrientsmentioning
confidence: 99%
“…Recently, it has been suggested that a reduction in dietary protein impacts pig's fat partitioning, with an increase in IMF and a minor effect on the amount of subcutaneous adipose tissue (SAT) Doran et al, 2006). Reducing the proportion of protein relative to energy in the diet consistently increases fat deposition, especially at the intramuscular level, because excess energy is diverted to fat deposition (Lebret et al, 2001;Wood et al, 2004).…”
Section: Introductionmentioning
confidence: 99%